Diagnóstico comunitario de salud del Barrio Motupe Bajo sector V, septiembre - diciembre del 2013 - Cuenca Cuenca, Johana Karina (2016)
The present titled study "DIAGNOSTIC COMMUNITY OF HEALTH OF THE NEIGHBORHOOD MOTUPE LOW SECTOR V, SEPTEMBER-DECEMBER OF 2013", it is framed in the macro-project INFIRMARY IN THE PARTICIPATION OF THE PATTERN OF INTEGRAL ATTENTION OF HEALTH MAIS UNIVERSITY HOSPITAL DE MOTUPE SEPTEMBER DECEMBER OF 2013, it seeks to contribute with the social development of the town, contributing statistical data; the same ones that will allow to the Teams of Health of the University Hospital of Motupe, to elaborate strategies for the maintenance and improvement of the health of people, families and communities, from a focus biopsicosocial, multidisciplinary and intercultural. The study was of Descriptive type, he/she makes emphasis in the analysis and interpretation of the facts; the methodology leaned on in strategies settled down in the Pattern of Integral Attention of Health, such as: It visits Domiciliary to apply the Family Record and it guides of interview that it allowed to complete the information for the base line, where high-priority problems were identified to take technical decisions and appropriate politicians to the local reality looking for to optimize the institutional answers and to propitiate the community participation in the improvement of the conditions of health. Among the most outstanding data indicators stand out as prevalencia of feminine sex, basic education level, was located nine illiterates, the economically active population is bricklayers, in school and adolescents are appreciated cases of overweight and all study, for the family planning in women in fertile age the method of the rhythm is the most used one and with regard to the epidemic profile of the chronic illnesses the HTA stands out, it was identified two people with discapacidad of visual type and intellectual. Words Key: Diagnostic community of health, Epidemic Profile.